Implementation of a consensus protocol for antibiotic use for bone and joint infection to reduce unnecessary outpatient parenteral antimicrobial therapy: A quality improvement initiative - Hiroyuki Suzuki; Hilary J. Mosher; Brett H. Heintz; Daniel J. Livorsi (Cambridge University Press, 2022)
Abstract Objective: We aimed to decrease the use of outpatient parenteral antimicrobial therapy (OPAT) for patients admitted for bone and joint infections (BJIs) by applying a consensus protocol to suggest oral antibiotics for BJI. Design: A quasi-experimental before-and-after study. Setting: Inpatient setting at a single medical center. Patients: All inpatients admitted with a BJI. Methods: We developed a consensus table of oral antibiotics for BJI among infectious diseases (ID) specialists. Using the consensus table, we implemented a protocol consisting of a weekly reminder e-mail and case-based discussion with the consulting ID physician. Outcomes of patients during the implementation period (November 1, 2020, to May 31, 2021) were compared with those during the preimplementation period (January 1, 2019, to October 31, 2020). Our primary outcome was the proportion of patients treated with OPAT. Secondary outcomes included length of hospital stay (LOS) and recurrence or death within 6 months. Results: In total, 77 patients during the preimplementation period and 22 patients during the implementation period were identified to have a BJI. During the preimplementation period, 70.1% of patients received OPAT, whereas only 31.8% of patients had OPAT during the implementation period (P = .003). The median LOS after final ID recommendation was significantly shorter during the implementation period (median 3 days versus 1 day; P < .001). We detected no significant difference in the 6-month rate of recurrence (24.7% vs 31.8%; P = .46) or mortality (9.1% vs 9.1%; P = 1.00). Conclusions: More patients admitted with BJIs were treated with oral antibiotics during the implementation phase of our quality improvement initiative.